2020
DOI: 10.1055/a-1301-0183
|View full text |Cite
|
Sign up to set email alerts
|

Infraspecific Chemical Variability and Biological Activity of Casearia sylvestris from Different Brazilian Biomes

Abstract: Casearia sylvestris is an outstanding representative of the Casearia genus. This representability comes from its distinctive chemical profile and pharmacological properties. This species is widespread from North to South America, occurring in all Brazilian biomes. Based on their morphology, 2 varieties are recognized: C. sylvestris var. sylvestris and C. sylvestris var. lingua. Despite the existence of data about their chemical composition, a deeper understanding of the specialized metabolism correlation and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…However, it is important to emphasize that the chemical diversity of a sample is highly influenced by many factors, such as genetic variation and environmental influences (soil nutrients, humidity, herbivory, and ecological interactions, among others; Isah, 2019 ). Studies have shown that even the same species collected in different biomes ( Bueno et al, 2021 ) or different seasons ( Zanatta et al, 2021 ) can produce different relative amounts of specific metabolites. Therefore, even for a single species, a range of factors can be explored to understand how the metabolites are affected to infer their possible ecological roles.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to emphasize that the chemical diversity of a sample is highly influenced by many factors, such as genetic variation and environmental influences (soil nutrients, humidity, herbivory, and ecological interactions, among others; Isah, 2019 ). Studies have shown that even the same species collected in different biomes ( Bueno et al, 2021 ) or different seasons ( Zanatta et al, 2021 ) can produce different relative amounts of specific metabolites. Therefore, even for a single species, a range of factors can be explored to understand how the metabolites are affected to infer their possible ecological roles.…”
Section: Resultsmentioning
confidence: 99%
“…Although many species may occur both in Cerrado and Atlantic Forest, the chemical profile of a particular species may vary depending on the collection site among other factors, such as seasonality and even day period due to the plant's circadian rhythm. Such observations have triggered interesting ecophysiological studies which evidenced infraspecific chemical variability as observed in Casearia sylvestris (Bueno et al 2021) and in the essential oil of leaves of Cryptocarya mandioccana (Telascrea et al 2007). Further interesting examples regarding ecophysiological interactions include those associated with chemical biology of plant-insect-parasites trophic systems, as in the study of the neotropical shrub Piper amalago, which showed how herbivory, caterpillar biodiversity and plant-herbivore network structure might be affected by the chemical profile and structural dimensions of phytochemical diversity (Cosmo et al 2021).…”
Section: Chemical and Biological Studies Regarding Brazilian Flora In...mentioning
confidence: 96%
“…The use of special phytochemicals to develop novel anti-oxidative, mitochondrial protection, and anti-apoptotic drugs on DA neurons may achieve the purpose of treating or curing PD. Narcissoside (NCS) ( Figure 1 ) is isolated from Sambucus nigra flowers (elderflowers), and has been reported to have several pharmacological activities, such as antioxidant [ 23 , 24 ], anti-inflammatory activities [ 25 ], anti-SARS-CoV-2 [ 26 ], antihypertensive properties [ 27 ], and antitumor potential [ 28 , 29 ]. It also activates TRPV1 channels in dorsal root ganglion sensory neurons linked with pain-accompanied itch [ 30 ].…”
Section: Introductionmentioning
confidence: 99%